The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1460-9568.1999.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and evoked activity of intercalated amygdala neurons

Abstract: The intercalated cell masses are clusters of GABAergic neurons interposed between the basolateral and centromedial nuclear groups of the amygdala. Tract-tracing studies have revealed that the main projection sites of intercalated neurons are the central amygdaloid nucleus and the basal forebrain. Through these projections, intercalated neurons could influence the activity of widespread regions of the central nervous system. However, no data are available regarding their physiological properties because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Although this possibility cannot be excluded at the present time, since anesthetics generally depress neuronal excitability, we would expect ITC cells to display even stronger IL responses and higher spontaneous firing rates in behaving animals. Consistent with this notion, a previous study in unanesthetized cats (Collins and Paré 1999) reported that ITC cells had much higher spontaneous firing rates than observed in the present study.…”
Section: Distinctive Responsiveness Of Itc Cells To Il Inputssupporting
confidence: 93%
See 2 more Smart Citations
“…Although this possibility cannot be excluded at the present time, since anesthetics generally depress neuronal excitability, we would expect ITC cells to display even stronger IL responses and higher spontaneous firing rates in behaving animals. Consistent with this notion, a previous study in unanesthetized cats (Collins and Paré 1999) reported that ITC cells had much higher spontaneous firing rates than observed in the present study.…”
Section: Distinctive Responsiveness Of Itc Cells To Il Inputssupporting
confidence: 93%
“…First, although experimental studies on extinction are typically performed in rats and mice, the majority of studies on ITC cells have been performed in guinea pigs and cats (Collins and Paré 1999;Smith 1993a, 1993b;Paré 2002, 2003;Royer et al 1999Royer et al , 2000aRoyer et al , 2002b, with few exceptions (Geracitano et al 2007;Marowsky et al 2005). As a result, it is currently unclear whether critical aspects of ITC connectivity also characterize commonly used rodent species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for these somewhat discrepant results may lie in the unique physiology of medial ICN neurons. These neurons are fast-spiking and respond to IL stimulation by firing high frequency spike bursts (Collins and Paré, 1999; Amir et al, 2011). Moreover, they exhibit an unusual slowly inactivating voltage-dependent potassium conductance (I SD ) which activates at subthreshold voltages and inactivates in response to depolarization (Royer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…According to a functional scheme proposed by Paré and colleagues (Collins and Paré 1999;Paré and Smith 1993;Royer et al 1999; reviewed by Davis and Whalen 2001), the lateral, basal, and accessory basal nuclei of the amygdala, evaluate the emotional valence of stimuli, whereas the central nucleus is the effector for an appropriate behavioral and autonomic response. Neurons in the central nucleus are involved in the initiation of somatic, autonomic, and endocrine responses to emotional stimuli (Kaada 1967;Kapp et al 1979;Moga and Gray 1985).…”
Section: Category-selective Neuronsmentioning
confidence: 99%